ERGONOMIC RISK FACTOR’S SAFETY SIGN: A REVIEW - Zulfahmi Noor; Ilham Bakri; Irwan Setiawan (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
One of the risks in the workplace today is the risk of ergonomic hazards, apart from the risks of hazards that often occur such as risks of physical hazards and risks of hazards from the work environment. If the risk of physical hazards and the risk of environmental hazards already have many safety signs that are widely accepted, this is not the case with the risk of ergonomic hazards that do not yet have a validated and widely used safety sign. More fundamentally, awareness of the risks of ergonomic hazards is not fully understood by both workers and employer institutions. The method used in reviewing this paper is to enter the keywords safety sign, safety sign design, and ergonomic risk factors on google scholar and science direct.